The Role of Management Accounting Information in Enhancing Business Decision-Making Effectiveness in Small and Medium-Sized Enterprises - Nur Asmi Ainun Kamal; Melsa Jumliana; Fika Hartina Sari; Rahadian Cahyadi; Sitti Jam'iah; Ari Sarwo Indah Safitri (Jurnal Ekonomi Balance, 2026)
Small and Medium Enterprises (SMEs) play a critical role in economic development, yet many SMEs face challenges in making effective business decisions due to limited use of structured accounting information. The availability of reliable management accounting information is therefore essential to support managerial planning, control, and strategic decision-making. This study aims to examine the role of management accounting information in supporting effective business decision-making processes in SMEs. The research employed a quantitative approach using a survey method involving 120 SME owners and managers who actively participate in managerial decision-making. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using descriptive statistics, validity and reliability tests, and simple linear regression analysis with the assistance of SPSS software. The results indicate that management accounting information has a positive and statistically significant influence on effective business decision-making in SMEs (β = 0.648, p < 0.001). The findings show that SMEs that utilize relevant, timely, and reliable accounting information demonstrate higher decision-making quality, improved strategic planning, and more efficient operational management. The study highlights that management accounting information functions as an important decision-support tool that reduces uncertainty and enables managers to evaluate business alternatives more effectively. The results contribute to the development of management accounting literature by emphasizing the decision-support role of accounting information in the SME context. Practically, the findings suggest that strengthening accounting practices and improving the accessibility of accounting information systems can enhance managerial capabilities and support sustainable business development among SMEs.